Colorimetric Assay for Antifungal Susceptibility Testing of Aspergillus Species - Meletiadis, Joseph (American Society for Microbiology, 2001)
A colorimetric assay for antifungal susceptibility testing of Aspergillus species (Aspergillus fumigatus, Aspergillus flavus, Aspergillus terreus, Aspergillus nidulans, and Aspergillus ustus) is described based on the reduction of the tetrazolium salt 2,3-bis(2-methoxy-4-nitro-5-[(sulphenylamino)carbonyl]-2H-tetrazolium-hydroxide (XTT) in the presence of menadione as an electron-coupling agent. The combination of 200 μg of XTT/ml with 25 μM menadione resulted in a high production of formazan within 2 h of exposure, allowing the detection of hyphae formed by low inocula of 10(2) CFU/ml after 24 h of incubation. Under these settings, the formazan production correlated linearly with the fungal biomass and less-variable concentration effect curves for amphotericin B and itraconazole were obtained.